2005
DOI: 10.2134/jeq2004.0364
|View full text |Cite
|
Sign up to set email alerts
|

Green Roof Stormwater Retention

Abstract: Urban areas generate considerably more stormwater runoff than natural areas of the same size due to a greater percentage of impervious surfaces that impede water infiltration. Roof surfaces account for a large portion of this impervious cover. Establishing vegetation on rooftops, known as green roofs, is one method of recovering lost green space that can aid in mitigating stormwater runoff. Two studies were performed using several roof platforms to quantify the effects of various treatments on stormwater reten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
100
2
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 480 publications
(168 citation statements)
references
References 12 publications
8
100
2
3
Order By: Relevance
“…Nevertheless, previous studies have demonstrated rainfall retention characteristics of green roofs (Mentens et al, 2006;Simmons et al, 2008;VanWoert et al, 2005). For example, VanWoert et al (2005) showed that for a 10 cm thick substrate and a heavy rainfall event, defined as exceeding 6 mm rainfall per day, 54% of precipitation is retained by the growth medium. To compute the change in runoff, we used the Natural Resource Conservation Service (NRCS) method for urban hydrology (NRCS, 1986).…”
Section: 1002/2017ef000536mentioning
confidence: 99%
“…Nevertheless, previous studies have demonstrated rainfall retention characteristics of green roofs (Mentens et al, 2006;Simmons et al, 2008;VanWoert et al, 2005). For example, VanWoert et al (2005) showed that for a 10 cm thick substrate and a heavy rainfall event, defined as exceeding 6 mm rainfall per day, 54% of precipitation is retained by the growth medium. To compute the change in runoff, we used the Natural Resource Conservation Service (NRCS) method for urban hydrology (NRCS, 1986).…”
Section: 1002/2017ef000536mentioning
confidence: 99%
“…Furthermore, green roofs can be retrofitted onto existing 189 buildings as well as incorporated into new developments (Castleton et al, 2010). This is 190 particularly beneficial in urban areas where roofs can account for a high proportion of 191 the total impervious land area (Carson et al, 2013;VanWoert et al, 2005). 192…”
Section: List Of Figures 23mentioning
confidence: 99%
“…From an energy prospective, green roofs also promote evaporative cooling, thereby offsetting the energy requirements associated with air conditioning systems and reducing urban heat island effects [6,7]. From a hydraulic perspective, several studies have shown that green roofs have significant effects on retaining rainfall volumes [8][9][10][11], delaying the peak flow rate [12,13] and reducing the runoff volume discharged into the combined sewer systems (CSSs) [14][15][16]. Many literature studies have, indeed, investigated the hydraulic efficiency of green roofs, but only few have focused on the performance of such systems under Mediterranean climate condition.…”
Section: Introductionmentioning
confidence: 99%